Novel technique for hill climbing search to reach maximum power point tracking - Ahmed Samir Badawi; Nurul Fadzlin Hasbullah; Siti Hajar Yusoff; Aisha H Hashim; Alhareth Zyoud (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
In this paper, a new technique has been proposed to solve the trade off common problem in hill climbing search algorithm (HCS) to reach maximum power point tracking (MPPT). The main aim of the new technique is to increase the power efficiency for the wind energy conversion system (WECS). The proposed technique has been combined the three-mode algorithm to be simpler. The novel algorithm is increasing the ability to reach the MPPT without delay. The novel algorithm shows fast tracking capability and enhanced stability under change wind speed conditions.